A rice Serine/Threonine receptor-like kinase regulates arbuscular mycorrhizal symbiosis at the peri-arbuscular membrane - Roth, Ronelle; Hillmer, Stefan; Schumacher, Karin (Nature Communications, 2018)
The peri-arbuscular membrane (PAM) mediates mutually-beneficial nutrient exchange between plants and arbuscular mycorrhizal (AM) fungi. Here the authors identify ARK1, a PAM-specific receptor-like kinase from rice that sustains AM symbiosis post-arbuscule development.
Gesehen am 18.04.2019